Position, Tenure And Responsibility Of The Notary In Carrying Out The Position Of Notary - IRIANTORO, Agung (Indonesia Strategic Sustainability, 2022)
Notary, as authentic deed-makers, has a vital role in people's lives. It is because society needs someone whose information is reliable and trustworthy, whose signature and seal (stamp) can provide solid guarantees and evidence, an impartial expert and an adviser who has no defects, who shuts up and makes an agreement that can protect in the days to come. The position of the notary must provide legal certainty services in the form of doing authentic deeds and making land deeds; in their duties, two main functions, namely the first notary has legal certainty responsibility to the public for any ratification of legal bindings, and the second is that the notary has the authority granted by law as a state official to provide legal reinforcement for legal bindings, which in the end gives peace and a sense of security to the community. The notary's responsibility is determined by the nature of the violation, the legal consequences it causes, and the potential mandatory risks. Therefore, Notaries, in carrying out their positions, doing authentic deeds, and others, apparently made mistakes, so what is used beeps fout is a unique term addressed to errors made by professionals with particular positions, such as Notaries whose mistakes are made carrying out the job.